Acupuncture during pregnancy and the perinatal period: Women's attitudes, beliefs and practices. Issue 3 (May 2020) - Williams, Heidi; Sweet, Linda; Graham, Kristen
Abstract: Background: Acupuncture during pregnancy and the perinatal period aims to increase normal birth and enhance a woman's birth experience by decreasing intervention and adverse birth outcomes. Acupuncture in Australian maternity services has not been well accepted, and there is limited research evidence as to whether women are supportive of acupuncture treatment. Objective: The aims of this study were to understand childbearing aged women's attitudes, beliefs and practices to using acupuncture during pregnancy and the perinatal period, and possible acceptance of a midwife providing acupuncture treatments. Design: A descriptive/explorative quantitative methodology was used to gather data from childbearing aged women using an online survey. Statistical analysis was used for quantitative data and content analysis for the free-text responses. Recruitment of respondents took place in 2017 via Facebook birth and parenting groups and pages. Findings: Of 304 respondents, 68% (n = 206) had used acupuncture, and of these, 68% (n = 140) used acupuncture for concerns during pregnancy and the perinatal period. The majority of respondents indicated they would consider acupuncture during pregnancy and the perinatal period (89%) and 62% indicated they would have a midwife provide a treatment. The free-text responses provided mostly positive comments on the outcomes and satisfaction of acupuncture treatments (84% n = 199). Conclusion: The majority of respondents would consider acupuncture during pregnancy and the perinatal period, were positive to trying acupuncture for various concerns, and were positive towards a midwife providing treatments. These findings raise awareness of women's desire for the choice of an acupuncture treatment during pregnancy and the perinatal period.